Non-Theological Factors That May Hinder or Accelerate the Church's Unity (The ecumenical review, 1952)
Note: Readers of the Review will remember the letter on “Unavowed Motives in Ecumenical Discussions” which Professor C. H. Dodd wrote in 1949 to the World Council's Commission on Faith and Order (Ecumenical Review, Autumn 1949). The Commission decided to put this question on the agenda of the Lund Conference on Faith and Order. A preliminary study conference on the subject was held by the American Committee for Faith and Order last summer. The fruit of their work was brought to another conference, primarily of European and British church members, which has been held at the Ecumenical Institute in November 1951. It has produced the following report which will be submitted to the Churches participating in the Lund Conference.